2010
DOI: 10.1007/s10528-010-9376-6
|View full text |Cite
|
Sign up to set email alerts
|

PON1 55 and 192 Gene Polymorphisms in Type 2 Diabetes Mellitus Patients in a Turkish Population

Abstract: Diabetes mellitus is a multifactorial metabolic disease, caused by the complete or relative absence of insulin hormone, which results in the deterioration of carbohydrate, protein, and lipid metabolism. The PON1 55 and 192 polymorphisms have been reported to be associated with type 2 diabetes and its complications. In this study, the involvement of the PON1 55 and 192 polymorphisms and paraoxonase enzyme activity in diabetic complications was assessed. The MM and QQ genotypes were the most frequent in complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 21 publications
(20 reference statements)
4
29
2
Order By: Relevance
“…It was 35.8% lower than that of the controls. This observation is similar to the previous studies (Agachan et al, 2004;Ergun et al, 2011;Inoue et al, 2000;Mackness et al, 1998;Sakai et al, 1998) which have been carried out in different populations. Low PONase activity decreases the ability to prevent lipid-peroxidation and could therefore be a reason for the accelerated atherosclerosis often reported in type 2 diabetes patients (Abbott et al, 1995).…”
Section: Ponase and Arease Activitiessupporting
confidence: 92%
See 1 more Smart Citation
“…It was 35.8% lower than that of the controls. This observation is similar to the previous studies (Agachan et al, 2004;Ergun et al, 2011;Inoue et al, 2000;Mackness et al, 1998;Sakai et al, 1998) which have been carried out in different populations. Low PONase activity decreases the ability to prevent lipid-peroxidation and could therefore be a reason for the accelerated atherosclerosis often reported in type 2 diabetes patients (Abbott et al, 1995).…”
Section: Ponase and Arease Activitiessupporting
confidence: 92%
“…PONase activity has been found to be decreased in patients with diabetes (Abbott et al, 1995;Altuner et al, 2011;Ergun et al, 2011;Mackness et al, 1998) and familial hyperlipdemia (Mackness et al, 1991b) which is associated with accelerated atherosclerosis. Decreased PONase activity in patients with type 2 diabetes could lead accelerated atherosclerosis and thereby increased mortality from coronary artery disease (CAD) (Haffner et al, 1998;Nathan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Human serum PON1 gene protects from atherosclerosis by preventing LDL-C from oxidation as well as by hydrolyzing the oxidized form of LDL-C. PONase activity has been found to be decreased in patients with diabetes (Altuner et al 2011;Ergun et al 2011) and familial hyperlipidemia. Nearly 200 single-nucleotide polymorphisms (SNPs) of PON1 gene have been identified so far (Richter et al 2010 [Costa et al2003].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a previous study has shown that the low serum paraoxonase activity associated with diabetes was not caused by phenotypic differences in the diabetic population when compared with healthy control subjects, nor it was due to a lower paraoxonase concentration in diabetics (14). But Altuner and Ergun claimed that lower PON activity showed in increased diabetic complication (39,40). …”
Section: Discussionmentioning
confidence: 97%